Study of the flora of the "Antonio Raimondi" National Ecological Park in Ancon, Lima - Peru - Merino Monterrey, Jo Annie (2023)
In September 2014, a study of the vegetation of the "Antonio Raimondi" Ecological National Park was conducted in the district of Ancon in Lima Metropolitan. The composition of flora species was recorded according to their classification by genera and families. Components including relative abundance, relative frequency, density, and vegetation cover were examined at for the quantitative evaluation. A total of 1050 individuals from 14 flora species and 1 morphospecies were registered, the 14 species were grouped into 7 families and 10 genera. The flora of the area was characterized by the species Tillandsia purpurea Ruiz & Pav. at 41.55%, Tillandsia latifolia Meyen at 24.23%, and Solanum multifidum Lam. at 14.02% as the most abundant. The Solanaceae family, represented by 3 species and the genera Solanum and Nicotiana had the most diversity. The species T. latifolia, T. purpurea, and Nicotiana paniculata L. were the most frequent, mainly present in Inocentes and Quebradilla Ravines. The species T. purpurea, followed by T. latifolia, had the highest densities. The "Tillandsias" and "Cactaceas" had the most vegetation coverage in the area, which was distributed in the central and northern zones, while the herbaceous vegetation had less coverage and was located in the southern part of the area. We identified 14 species; 3 of them were under threat categories, and 9 of them presented endemism. The Cactaceae family had 2 Endangered species and 1 specie would be classified as Critically Endangered or Vulnerable. The study area is being planned by the central government as a sustainable city, therefore knowing the flora and its plant communities will provide tools for its conservation and incorporation into urban planning.